PENGARUH KEPERCAYAAN KONSUMEN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN MENGGUNAKAN JASA TRANSPORTASI ONLINE GO-JEK PADA MASA PANDEMI COVID-19 (STUDI KASUS PADA PENGGUNA GO-JEK DI KABUPATEN KARAWANG) - Windi Andriani; Reminta Lumban Batu (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
This research was conducted with the aim to know the influence of consumer trust and service quality on consumer loyalty using gojek online transportation services during the covid-19 pandemic (a case study on gojek online transportation users in Karawang Regency), either partially or simultaneously. This hold as an associative research using a quantitative approach. The sample selection is non probability sampling with purposive sampling technique, gathering 96 respondents. The data is collected through a questionnaire that has been tested for validity and reliability. The technique of analyzing the data is partial using descriptive data analysis, multiple linear regression analysis, and significant test (Classical Assumption Test, t Test and F Test). The results of this study indicate the probability value (sig) is 0,000 <0,05 simultaneous. This proves that consumer trust and service quality have a significant simultaneous effect on consumer loyalty of gojek online transportation services during the covid-19 pandemic. It is concluded that consumer trust has no significant effect on consumer loyalty with a probability value (sig) of 0,899 > 0,05, while service quality has a significant effect on consumer loyalty with a probability value (sig) of 0,000 < 0,05.